Enhanced Mechanical Properties of Fe-Mn-Al-C Low Density Steel via Aging Treatment - Kang, Li; Yuan, Hao; Li, Hua-ying; Ji, Ya-feng; liu, Hai-tao; Liu, Guang-ming (Frontiers in Materials, 2021)
The tensile properties and deformation behavior of an aged Fe-25Mn-6Al-1C (mass%) alloy with an stacking fault energy of approximately 60 mJ·m-2 were investigated. The results show that an ordered phase with an “short-range ordering” (SRO) structure formed after aging at 550 oC for 10 h; with further increasing the aging time to 48 h, the lamellar second-phase precipitates appeared at the austenitic grain boundaries. The aged sample at 550 oC for 10 h exhibited an enhanced tensile strength (~898 MPa) without notably sacrificing uniform elongation (~46.3%), which was mainly attributed to the relatively high strain hardening in the entire plastic deformation due to the synergistic effects of planar slip, twinning-induced plasticity (TWIP), microband-induced plasticity (MBIP), and especially for the formation of short-range ordering.